Thermal structure of Venus nightside upper atmosphere measured by stellar occultations with SPICAV/Venus Express. (August 2015) - Piccialli, A.; Montmessin, F.; Belyaev, D.; Mahieux, A.; Fedorova, A.; Marcq, E.; Bertaux, J.-L.; Tellmann, S.; Vandaele, A.C.; Korablev, O.
Abstract: The thermal structure of Venus upper atmosphere (90–140 km) was investigated using stellar occultation measurements acquired by the SPICAV experiment on board Venus Express. The SPICAV ultraviolet channel provides CO2 local density and temperature vertical profiles with a vertical resolution of < 7 km of both the southern and the northern hemispheres on the nightside (18:00–06:00 h local time). A permanent layer of warm air is observed at the mesopause in the altitude range 90–100 km. Temperature then decreases with increasing altitude reaching a minimum value around 125 km. Spatial and temporal changes in the thermal structure have been analyzed. Local time variations dominate the structure of Venus atmosphere at these altitudes: temperatures show an increase of ~ 20 K on the morning side compared to the evening side. The homopause altitude was also determined; it varies between 119 and 138 km of altitude, increasing from the evening side to the morning side. SPICAV temperature profiles were compared to several literature results from ground-based observations, previous spacecraft missions and the Venus Express mission. Abstract : Highlights: The thermal structure of Venus nightside upper atmosphere (90–140 km) was investigated. Stellar occultation measurements acquired by the SPICAV experiment on board Venus Express were used for this study. A permanent layer of warm air is observed at the mesopause in the altitude range 90–100 km. Local time variations dominate the structure of Venus atmosphere at these altitudes (90–140 km). SPICAV temperature profiles were compared to several published results from ground-based observations, previous spacecraft missions and the VEx mission.